The principle of proportionality as an objective justification for restrictions on the free movement of persons in the European Union - Ryszka, Joanna (The Opole Studies in Administration and Law, 2016)
The principle of proportionality in the EU legal order applies, among others, to actions taken by Member States in the situation where they are willing to use, permitted by the EU law, derogation from its provisions, in particular – in the area of internal market freedoms. Derogation from those freedoms will not be justified if it is not absolutely necessary. National regulations must therefore be proportionate to the objective that these restrictions are to protect. With respect to the free movement of persons, as an example of these goals, the protection of fundamental rights could be mentioned. It is vitally important for the realization of an internal market due to the existence of interesting interactions occurring between them and specific ways of applying the principle of proportionality when they collide with each other.